Concentric magnetic gear structure review - Mohd Ab Halim, Mohd Firdaus; Ab Rahman, Azhan; Sulaiman, Erwan (Wydawnictwo SIGMA-NOT, 2024)
The paper presents the evolvement of magnetic gear structure from its inception up to the year of 2023. The output performances (power and torque) of all the structure will be tabled and analyzed in this paper. Among several structures researched in MG, Concentric Magnetic Gear (CMG), is the most researched structure due to its high utilization of the magnetic field compared to other structure. Since many structure evolved from CMG, a classification tree derived from CMG is presented. The classification tree provides an overview of the state of the art in CMG design.